(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Aging and degeneration are natural course of life, but in this modern era the advancement of technologies and busy life style contribute to the early degeneration process. Improper continuous postures, jerky movements while travelling, overuse of mobiles etc. will produce undue pressure and stress to the cervical disc and it will lead to inflammatory reaction and eventually degeneration. Cervical spondylosis caused by wear and tear phenomena in cervical spine. It is most frequently involved in the cartilage and bones of the cervical spine and causes loss of normal spine function. According to Ayurvedic perspectives cervical spondylosis can be correlated with Asthigata Vata. A female patient age 23yrs., diagnosed and non-operated case of Cervical spondylosis (19/07/2023 OPD NO.27393, IPD NO. 2150) came to Panchakarma OPD of ITRA, Jamnagar with complaints of pain at nape of neck radiating to right upper limb (Greeva Shoola) since last 5yrs along with restricted ROM of neck (Greeva Stambha) and difficulty in doing daily activities such as reading, etc. The pain aggravated in prolonged reading and morning. She was treated with Valuka Swedana for 3 days followed by Greeva Basti with Ksheera Bala Taila 14 days along with physiotherapy (isometric exercise of neck) and Abha Guggulu. Significant improvements were observed in various subjective and objective parameters after the treatment.